2013
DOI: 10.1111/imre.12022
|View full text |Cite
|
Sign up to set email alerts
|

Unauthorized Immigration to the United States: Annual Estimates and Components of Change, by State, 1990 to 2010

Abstract: We describe a method for producing annual estimates of the unauthorized immigrant population in the United Sates and components of population change, for each state and D.C., for 1990 to 2010. We quantify a sharp drop in the number of unauthorized immigrants arriving since 2000, and we demonstrate the role of departures from the population (emigration, adjustment to legal status, removal by the Department of Homeland Security (DHS), and deaths) in reducing population growth from one million in 2000 to populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
126
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(132 citation statements)
references
References 17 publications
4
126
1
1
Order By: Relevance
“…As a result, researchers need to rely on imputations of undocumented status. These imputation methods have evolved considerably over the last few decades Cohn 2009, Warren andWarren 2013). However, some authors have shown that these imputations can lead to large bias in some applications (van Hook et al 2015).…”
Section: Undocumented Students In Higher Educationmentioning
confidence: 99%
“…As a result, researchers need to rely on imputations of undocumented status. These imputation methods have evolved considerably over the last few decades Cohn 2009, Warren andWarren 2013). However, some authors have shown that these imputations can lead to large bias in some applications (van Hook et al 2015).…”
Section: Undocumented Students In Higher Educationmentioning
confidence: 99%
“…U.S. government surveys do not ask about immigrants' legal status. Instead, we use state-level estimates of unauthorized immigrants from Warren and Warren (2013), multiplied by the proportion of immigrants who are Mexican (according to the state-year cell of the CPS panel)…”
Section: Resultsmentioning
confidence: 99%
“…In these regressions, we replace controls for the Mexican immigrant unemployment rate and hourly wage with those for the relevant subpopulation, but all other covariates are unchanged. In columns (1)- (2), we analyze shares of all non-Mexican immigrants and non-Mexican unauthorized immigrants, respectively, where the latter are constructed by multiplying the Warren and Warren (2013) estimates by the state's proportion of immigrants who are non-Mexican. In both cases, the OLS and IV coefficients are statistically indistinguishable from zero, in contrast to our earlier findings for Mexican immigrants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations